Industry Competencies and the Optimal Hospitality Management Curriculum: An Empirical Study. Issue 4 (2nd October 2019) - Alexakis, George; Jiang, Lan
ABSTRACT: The purposes of this study were to investigate hospitality managers' perceptions of the skills and knowledge of hospitality students and compare them to U.S. hospitality management undergraduate curricula. The responses of 206 surveyed managers who rated the importance of 19 skill/knowledge items were used for the analysis. To identify program skill/knowledge sets, we selected curricula from 20 leading U.S. hospitality programs and compared them to the survey results. The curriculum inquiry indicated that all programs primarily focused on teaching professional skills for various hospitality concentrations. The results suggest that the emphasis on essential competencies of communication skills and higher learning skills such as critical thinking and problem solving should remain. The current study developed a model summarizing the type of skills/knowledge that are needed from hospitality students to meet the needs of entry-level management. The content analysis results fill the gap between the hospitality education and industry on curriculum and industry requirements.